Strontium isotopes – A tracer for river suspended iron aggregates. (April 2017) - Wortberg, Katharina; Conrad, Sarah; Andersson, Per S.; Ingri, Johan
Abstract: The Kalix River shows distinct temporal variations in the Sr-isotope ratio in filtered water (0.726–0.732). During base flow in winter the 87 Sr/ 86 Sr ratio is on average 0.730. When discharge increases and peaks during spring flood the 87 Sr/ 86 Sr ratio shows the most radiogenic (0.732) values. The temporal variations in the 87 Sr/ 86 Sr ratio in the Kalix River can be explained by mixing of water from the woodlands and the mountain areas. During high water discharge in May the 87 Sr/ 86 Sr ratios are more radiogenic in the suspended phase (1 kDa - 70 μm) compared to the truly dissolved phase (<1 kDa). The difference in 87 Sr/ 86 Sr ratio between the two phases (Δ 87 Sr/ 86 Sr) is linearly correlated with the suspended iron concentration. During spring flood Sr and Fe derived from an additional source, reach the river. Deep groundwater has a more radiogenic 87 Sr/ 86 Sr isotope ratio than the Kalix River during spring flood and thus, represents a possible source for the suspended Fe and the associated Sr. Strontium can be coprecipitated with and adsorbed to different types of Fe aggregates. We propose that the Sr-isotope ratio in the suspended phase reflects the isotopic composition of the water at the interface between anoxic groundwater and oxic stream water in the riparian zone, where the Fe aggregates are formed. These particles dominate the suspended phase in the river and the mixing with mountain waters, poor in Fe, produces the difference in the isotopic signature. The different signatures in suspended and truly dissolved fraction indicate that these aggregates are relatively stable during stream-river transport. As such the 87 Sr/ 86 Sr can be used to trace the origin of the non-detrital suspended phase. Highlights: The 87 Sr/ 86 Sr ratio is strongly bound to discharge changes; most radiogenic during peak spring discharge. The suspended phase (1 kDa–70 μm) is more radiogenic during spring discharge than the truly dissolved phase (<1 kDa). This difference is linearly correlated with the suspended iron concentration. Strontium isotopes appear to trace input of deep groundwater in boreal streams.